1999
DOI: 10.1164/ajrccm.160.6.9811054
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related Breathing Disorder Is an Independent Risk Factor for Systemic Hypertension

Abstract: The exact influence of sleep-related breathing disorder (SRBD) on blood pressure control remains unknown. We investigated the influence of different degrees of SRBD on daytime blood pressure and its association to documented hypertension by examining 1,190 consecutive patients referred for diagnosis of SRBD. The protocol includes clinical interview, physical examination, office blood pressure measurement, cholesterol, and blood gas analysis. Unattended home monitoring of nocturnal breathing was performed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(112 citation statements)
references
References 34 publications
2
102
0
8
Order By: Relevance
“…Some scientific evidence suggests that changes in breathing control may also be regarded as a risk factor associated with lifestyle in hypertensive patients 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scientific evidence suggests that changes in breathing control may also be regarded as a risk factor associated with lifestyle in hypertensive patients 20 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Brooks et al 25 , these changes in blood pressure control occur both during sleep and daytime, thereby suggesting a causal role of sleep breathing disorders in the development and maintenance of hypertension. Other than that, epidemiological studies show that sleep-disordered breathing is highly prevalent among hypertensive patients 26,27 , and also that 50 to 80% of the patients who experience such changes are hypertensive 20 . In this regard, the causal relationship of respiratory disorders might become confusing or disappear when age, obesity prevalence, smoking status, and alcohol consumption are taken into account in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it may be speculated that remaining RDI under CPAP is an important determinant for the extent of a preventive effect. Two large cross-sectional studies have demonstrated an independent dose-response relationship between RDI and systolic/diastolic blood pressure [23,24]. As for cardiovascular morbidity and mortality in OSA, there is increasing evidence, that nCPAP may have beneficial effects [7, 25±27].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the arousal remains below the level of consciousness, the temporal sequence of sleep stages is severely disrupted and the restorative function of sleep is destroyed. Sleep apnea is regarded as an independent risk factor for systemic hypertension (Grote et al, 1999).…”
Section: Obstructive Sleep Apnea As a Model Sleep Disordermentioning
confidence: 99%